Biblioteca 4.0 inteligente: um olhar sobre as bibliotecas universitárias brasileiras - Souza, Liliane Braga Rolim Holanda de (2023)
The term ‘Library 4.0’ has emerged as a designation possibility for new generation libraries that are based on advanced technologies arising from Web 4.0 and Industry 4.0 to design their facilities, products and services. Therefore, the hypothesis supported in the study is that Brazilian university libraries need to know the possibilities brought by the technologies and services of each generation, aiming to be ready to adopt the attributes of Library 4.0, as a way of developing and evolving as libraries intelligent in light of the context and needs of contemporary users. Thus, the general objective of the study is to analyze Brazilian university libraries, represented by the federal ones in the Northeast, from the perspective of Smart Libraries 4.0. From a methodological point of view, this is a practical research, whose research corpus is the university libraries belonging to federal universities in the Northeast, adopting the following collection procedures: bibliographic research, application of an online questionnaire to library system managers and the indexical method with the brazing technique. To analyze the data, content analysis is used. The analysis and discussion of the results show the attributes of the circulation and information dissemination and transfer service existing in Brazilian university libraries in the Northeast from the perspective of Smart Library 4.0. It also presents the perception of managing librarians on the topic and proposes guidelines for the creation of intelligent Libraries 4.0 in accordance with the Brazilian reality. The final considerations mention that the theoretical and applied research undertaken shows that some of the intelligent 4.0 attributes already exist in the national scenario of federal university libraries and, many other services/technologies and trends are already present in society and becoming increasingly popular. As it is a relatively new subject in the field of Library Science and Information Science, there is a need for more studies on the subject, focusing on other perspectives and with new theoretical and practical proposals. University libraries must be aware of changes in technologies, society, education and science to adopt strategies to act as Smart Libraries 4.0, which is technological, innovative and aligned with contemporary trends in sustainability, inclusion, education, diversity and collaboration in their facilities, products and services, based on the commitment to be an agent of transformation for development and quality of life.